Immigration Policy Challenges and Opportunities in Facing Illegal Migration - Daffa Raihan Arya Mas'adi (Cahaya Abadi Publisher, 2025)
Illegal migration is a global phenomenon that continues to be of concern to various countries because of its impact on social stability, the economy and national security. Immigration policy has an important role in managing illegal migration flows through various strategies, including border control, international cooperation, and the use of technology. However, policies that are too restrictive can cause negative impacts, such as increased human trafficking and exploitation of migrant workers. On the other hand, illegal migration also provides economic opportunities, such as meeting labor needs and increasing remittances for the country of origin. This research uses a qualitative approach with descriptive-analytical methods. Data was collected through a literature study which included analysis of immigration policy documents, reports from related institutions, as well as previous research on illegal migration. In addition, semi-structured interviews were conducted with various stakeholders, such as immigration officials, academics and international organizations working in the field of migration. The data analysis technique used is content analysis, which allows identifying patterns, trends and policy implications for the effectiveness of managing illegal migration. The research results show that effective immigration policies must balance law enforcement, protection of human rights, and the use of digital technology to improve immigration monitoring and services. With a comprehensive and adaptive approach, immigration policy can become a more effective instrument in facing the challenge of illegal migration in a sustainable manner.